Evaluation of three tropical starches as polymers for the formulation of diclofenac microspheres - Olufunke C. Babalola; Oluwatoyin A. Odeku; Alf Lamprecht (German Journal of Pharmaceuticals and Biomaterials, 2022)
Starches are derived from three botanical sources, such as unripe mature banana fruits (Musa sapientum L.), cocoyam (Colocasia esculenta L. Schott), and bitter yam (Dioscorea dumetorum Pax) tubers, have been evaluated as polymers in the design of microspheres incorporating diclofenac sodium as a model drug. Using the ionic gelation process, the starches were pregelatinized and used as polymers in conjunction with sodium alginate to produce diclofenac sodium microspheres with 2% calcium chloride as a crosslinking agent. The morphology, swelling properties, Entrapment Efficiency (EE), and drug release properties of the microspheres were evaluated. Fitting the in-vitro dissolution data into multiple kinetic models yielded the drug release pathways. Spherical discrete microspheres with rough surfaces were obtained with diameters ranging from 580 µm to 670 µm and EEs ranging from 68.0% to 80.7% w/w. For more than 5 hours, diclofenac sodium was released in a controlled manner. The type and concentration of starch in the polymer blend affected drug release from the microspheres, with banana starch at a 4:1 ratio demonstrating the slowest dissolution rate. Drug release from microspheres is best described by the Korsmeyer-Peppas model, which implies that drug release is governed by both diffusion and erosion mechanisms. The finding shows that tropical starches could be used to develop diclofenac sodium microspheres with controlled release.